Implementation of Artificial Intelligence on Indonesia’s Defense Intelligence Activities - Ramadhianto, Rizky; Toruan, Tahan Samuel Lumban; Kertopati, Susaningtyas Nefo Handayani; Almubaroq, Hikmat Zakky (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2023)
The global dynamics nowadays are synonymous with technological developments which have led to the complexity of emerging threats for implementing Indonesia's defense that come from state actors and non-state actors by taking advantage of technological advances in every digital-based crime. To respond, the concept of digital transformation needs to be realized in a more simultaneous and integrated manner for the defense process through technology platforms. One of them is using Artificial Intelligence technology on defense intelligence activities digitally to prevent sudden strategic attacks on defense forces. Despite of benefits that help intelligence performance in the defense sector, applying Artificial Intelligence technology has potential negative impacts. This article aims to study the significant implications of Artificial Intelligence technology on national defense using a qualitative descriptive method in literacy studies originating from journals, books, and credible internet sources. The findings provide that potential threats from Artificial Intelligence-based defense intelligence activities include miscalculation of algorithmic processes in the intelligence collecting phase, breaches in the process of sharing strategic defense data, and errors in processing statistical data as an effort to observe the reactions of other countries to maintain the balance of defense forces, resulting of misinterpretation in order to estimate national power of them and their intentions in deploying military force. If the potential threats are not focused on being addressed, it will have an impact on reducing the effectiveness of defense intelligence to reduce uncertainty in forecasting global threats.